Carica papaya extract in dengue: a systematic review and meta-analysis - Senaka Rajapakse; Nipun Lakshitha de Silva; Praveen Weeratunga; Chaturaka Rodrigo; Chathurani Sigera; Sumadhya Deepika Fernando (BMC, 2019)
Abstract Background Carica papaya (CP) extract is becoming popular as an unlicensed herbal remedy purported to hasten recovery in dengue infection, mostly based on observations that it may increase platelet counts. This systematic review and meta-analysis aims to critically analyze the evidence from controlled clinical trials on the efficacy and safety of CP extract in the treatment of dengue infection. Methods PubMed, LILACS and Google Scholar were searched for randomized or non-randomized trials enrolling patients with suspected or confirmed dengue where CP extract was compared, as a treatment measure, against standard treatment. Recovery of platelet counts as well as other clinical indicators of favourable outcome (duration of hospital stay, prevention of plasma leakage, life threatening complications, and mortality) were assessed. Results Nine studies (India-6, Pakistan-1, Indonesia-1, Malaysia-1) met the inclusion criteria. Seven studies showed an increase in platelet counts in patients receiving CP extract, while one study showed no significant difference between the two groups, and direct comparison was not possible in the remaining study. Serious adverse events were not reported. CP extract may reduce the duration of hospital stay (mean difference − 1.98 days, 95% confidence interval − 1.83 to − 2.12, 3 studies, 580 participants, low quality evidence), and cause improvement in mean platelet counts between the first and fifth day of treatment (mean difference 35.45, 95% confidence interval 23.74 to 47.15, 3 studies, 129 participants, low quality evidence). No evidence was available regarding other clinical outcomes. Conclusions The clinical value of improvement in platelet count or early discharge is unclear in the absence of more robust indicators of favourable clinical outcome. Current evidence is insufficient to comment on the role of CP extract in dengue. There is a need for further well designed clinical trials examining the effect of CP on platelet counts, plasma leakage, other serious manifestations of dengue, and mortality, with clearly defined outcome measures.